2018
DOI: 10.11591/ijece.v8i5.pp3536-3543
|View full text |Cite
|
Sign up to set email alerts
|

Design and Simulation of Novel 11-level Inverter Scheme with Reduced Switches

Abstract: This work recommends the performance of coupled inductor based novel 11-level inverter with reduced number of switches. The inverter which engender the sinusoidal output voltage by the use of split inductor with minimised total harmonic distortion (THD). The voltage stress on each controlled switching devices, capacitor balancing and switching losses can be reduced. The proposed system which gives better controlled output current and improved output voltage with moderate THD value. The switching devices of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…where Q is quality factor 20<Q<100 (7) the range of quality factor for a single tuned filter is considered as 20, R=1.41Ω.…”
Section: Lc Filter With Damping Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…where Q is quality factor 20<Q<100 (7) the range of quality factor for a single tuned filter is considered as 20, R=1.41Ω.…”
Section: Lc Filter With Damping Resistancementioning
confidence: 99%
“…Circuit model of five level multilevel inverter with voltage levels Shanono et al [6] four passive filters i.e., LC, LCL, and LCL with series and parallel resistance is compared for nine level inverters to obtain THD less than 5%. This problem of poor stability margin was addressed by connecting an appropriate resistance value in either series or parallel to the filter capacitance [7] the size of the filter is reduced by decreasing dv/dt stress. Therefore, the discussion suggested that there is an ample of scope for researchers in the field of cascaded H-bridge MLI.…”
Section: Introductionmentioning
confidence: 99%
“…Real objects may now be controlled remotely using internet connections, allowing for constant monitoring of solar panels to meet the rising need for electricity. Compared to nuclear power facilities, solar panels produce 300 times more hazardous waste per unit of electricity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Inverters have been used to get a sinusoidal wave by converting DC to AC waveform. Though twolevel and three-level inverters are most common in academic research and industrial use purposes, multilevel inverters (MLI) are often preferred for their number of voltages steps, because it assists to make a sinusoidal wave of output voltage or current [1]. Nowadays, wide-bandgap semiconductors materials are used for the operation of higher voltages and frequencies as it has many advantages.…”
Section: Introductionmentioning
confidence: 99%